Temperatura e precificação de ativos: um ensaio para o Brasil - Silva, Ricardo Ferraro Gilaberte da (2010)
We examinate the relationship between temperature anomalies and direct insurance claims from brazilian insurance market, as well as their effect on a consumption asset pricing model. To accomplish this, we have studied the effect of the claims and temperature anomalies in the opportunities of future investments. We tested a consumption asset pricing model using brazilian time series. Two consumption, two direct insurance claims and four temperature anomalies series were used in these tests. All series belongs to the interval between september 1996 and december 2007, in a quarterly frequency, two years after the beginning of Real plan and one year before the beggining of the credit crisis of 2008. In some cases we used monthly series. We observed positive and significative correlation between direct claims and temperature anomalies. Two models were better than CCAPM. The first with the growth rate of direct claims and the second with the temperature anomalies series elaborated by Goddard Institute of Space Sciences (GISS/NASA). As a result we observed that GISS temperature anomaly series elaborated by GISS is able to affect the future investment opportunities in brazilian capital market